1988
DOI: 10.1557/proc-127-373
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Prediction of Corrosion of Stainless Steel Nuclear Waste Canisters

Abstract: In this paper, we describe the preliminary stages of the development of a mathematical model of the evolution of the solution chemistry within a corroding crevice on passive stainless steel. It is based on a formulation by Oldfield and Sutton [1], but models the physical and chemical processes which determine the crevice solution in a more rigorous manner. The model will eventually be used to assess whether a ‘critical solution composition’, which results in the depassivation of the crevice and the onset of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Microbiological organisms that produce acid-forming metabolism products would also result in more aggressive environmental conditions. Sharland and Newton [48] have tried to determine a "critical" solution composition which results in the breakdown of the passive frlm within the crevice, and whether such a condition is achievable for a range of repository conditions, types of steels and canister designs.…”
Section: Localized Corrosionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbiological organisms that produce acid-forming metabolism products would also result in more aggressive environmental conditions. Sharland and Newton [48] have tried to determine a "critical" solution composition which results in the breakdown of the passive frlm within the crevice, and whether such a condition is achievable for a range of repository conditions, types of steels and canister designs.…”
Section: Localized Corrosionmentioning
confidence: 99%
“…During handling and emplacement of containers, it is important to limit the amount of scratches and other surface defects so as to lessen the number of sites on the container surface that would be prone to localized corrosion. It has been suggested that crevice attack initiates more easily than pitting corrosion on stainless steel [48]. The crevice corrosion rate for low carbon structural steels can be as high as 15 times the general corrosion rate in wet steam conditions [33].…”
Section: A Crevice Corrosionmentioning
confidence: 99%
See 1 more Smart Citation